Perception and Use of Complementary and Alternative Medicine (CAM) among undergraduate students in a Nigerian University - Ufuoma Shalom Ahwinahwi, Kingsley Chukwudi (Journal of Applied Pharmaceutical Science, 2016)
Objectives: This study was designed to evaluate the Perception and Use of Complementary and Alternative Medicines (CAM) among the undergraduate Students of Delta State University (DELSU), Abraka.-Nigeria. Methods: Self- administered questionnaires were distributed randomly to the participants. Result: Out of 450 students that voluntarily participated in the study, 368 (81.78%) had used or were currently using at least one of the various CAM modalities; Family members (282, 37.15%) appeared to be the most common source of information and knowledge about CAM while Herbal medicine (250, 37.71%) was the most commonly used and perceived to be the most effective CAM method, and the most popular ailment effectively treated with CAM was Malaria (142, 34.22%). Pharmacists (98, 45.80%) played a major role in influencing their perceptions towards CAM use and the major reason for CAM use was that CAM is Cheaper (159, 27.09%) than Conventional medicine, however, lack of scientific evidence to support CAM practices (340, 31.66%) was obtained as the most prevailing barrier to CAM use.Conclusion: Majority of undergraduate Students of DELSU used CAM and possessed positive perceptions of Complementary and Alternative medicine. Concerted efforts should therefore be made by members of the healthcare team to ensure the safety of these modalities.
Keywords: Undergraduate Students, Perception, Use, CAM.